Perencanaan Tebal Perkerasan Jalan Lingkar Perkantoran Gunung Gare Kota Pagar Alam - Andy Pawaka; Masagus Taswin (JURNAL ILMIAH BERING'S, 2016)
Highway as one of the means of transportation, construction of highways which is a priority scale of development in City Pagar Alam. Along with the rapid development, so can increasing of vehicle owners in Pagar Alam City. Planning of road construction of Gunung Gare office area in Pagar Alam City. The purpose of this study was to find out how much the carrying capacity of the land on the road construction and analyze the pavement thickness of the Gunung Gare Office Ring Road segment in Pagar Alam City to the volume of vehicles through it so that it can produce pavement thickness according to Bina Marga standards. The method used to determine the required pavement thickness above the layer which has a certain CBR value is by testing the CBR value in laboratory manner. The results of the study were to calculate the carrying capacity of the soil on the asphalt road that for pavement thickness each D1 was taken 5 cm and D2 taken 10 cm, and pavement thickness of Purnalam Gare City Gunung Gare pavement thickness with a 10 year plan life, for D3 pavement layer is 13 cm. The results of the analysis of pavement thickness on the circumference the office of Gunung Gare in Pagar Alam City based on the volume of vehicles through which meet the requirements according to the type of material used.